2012
DOI: 10.1186/1756-0500-5-36
|View full text |Cite
|
Sign up to set email alerts
|

The association of Toll-like receptor 4 gene polymorphisms with the development of emphysema in Japanese subjects: a case control study

Abstract: BackgroundThe principal role of Toll-like receptor 4 (TLR4) is the induction of immune responses to lipopolysaccharides. Previously, mice deficient in the TLR4 gene exhibited up-regulation of the NADPH oxidase system in the lungs. This resulted in increased oxidant generation and elastolytic activity, which led to pulmonary emphysema. It was suggested that TLR4 might maintain constitutive lung integrity by modulating oxidant generation. We investigated whether single nucleotide polymorphisms (SNPs) in the TLR4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The SNP rs1156889 is located in the 3′-UTR of the TLR4 gene, where the sequence may influence mRNA stability, translation and localization and thereby regulate expression of the gene and interfere with the host immune system. In previous studies, the rs11536889 C was showed to be significantly associated with a high risk of emphysema (Ito et al 2012 ) and prostate cancer (Kim et al 2012 ). However, our study did not find any significant association between this SNP and CAD, relating to allele, genotype and haplotype analysis.…”
Section: Discussionmentioning
confidence: 91%
“…The SNP rs1156889 is located in the 3′-UTR of the TLR4 gene, where the sequence may influence mRNA stability, translation and localization and thereby regulate expression of the gene and interfere with the host immune system. In previous studies, the rs11536889 C was showed to be significantly associated with a high risk of emphysema (Ito et al 2012 ) and prostate cancer (Kim et al 2012 ). However, our study did not find any significant association between this SNP and CAD, relating to allele, genotype and haplotype analysis.…”
Section: Discussionmentioning
confidence: 91%
“…did not find a change in frequency of TLR4(Asp299Gly) in COPD, while a later investigation described decreased frequency of this allele in COPD [ 15 , 17 ]. TLR4 polymorphism (rs11536889) was also associated with COPD in a Japanese population [ 31 ]. Others have found increased frequency of TLR4(T399I) and TLR9(T1486C) in COPD [ 16 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might impair function of the TLR4 molecule and interfere with the host innate immunity. Interestingly, this allele was previously demonstrated to be associated with the risk of developing emphysema [35], severe periodontitis [36], and gastric atrophy in Helicobacter pylori-seropositive subjects [37]. However, this variant was not associated with autoimmune pancreatitis [38] or sarcoidosis-related uveitis [39].…”
Section: Discussionmentioning
confidence: 99%